The Self-Confidence in Public Speaking of the English Department Students of Sriwijaya State Polytechnic - Salsabilah; Darmaliana; Eli Yeny; Munaja Rahma (HOLISTICS, 2021)
This research was conducted to find out the self-confidence in public speaking sixth-semester students in English Department of Sriwijaya State Polytechnic. This research used a quantitative method. A readymade questionnaire was used in collecting the data. The population was sixth-semester students at English Department of Sriwijaya State Polytechnic in 2018. By using purposive sampling, there were 50 participants who answered the questionnaires. The result showed the percentage of self-confidence in the sixth semester students’ public speaking in English Department of Sriwijaya State Polytechnic. The findings revealed that the students had high confidence to speak in public. This was supported by the results of a questionnaire that revealed the percentage of self-confidence in public speaking for sixth semester students in English Department of Sriwijaya State Polytechnic reaching 80,18%. Keywords: Public speaking, self-confidence